2005
DOI: 10.1038/sj.cdd.4401816
|View full text |Cite
|
Sign up to set email alerts
|

Matrix changes induced by transglutaminase 2 lead to inhibition of angiogenesis and tumor growth

Abstract: Administration of active TG2 to two different in vitro angiogenesis assays resulted in the accumulation of a complex extracellular matrix (ECM) leading to the suppression of endothelial tube formation without causing cell death. Matrix accumulation was accompanied by a decreased rate of ECM turnover, with increased resistance to matrix metalloproteinase-1. Intratumor injection of TG2 into mice bearing CT26 colon carcinoma tumors demonstrated a reduction in tumor growth, and in some cases tumor regression. In T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 36 publications
(55 reference statements)
8
108
0
Order By: Relevance
“…Because TG2 has been demonstrated to suppress tumor growth, metastasis, and angiogenesis in animal models of colon cancer and melanoma (36,37), our findings highlight TG2 as a potential drug development target for the treatment of cancers overexpressing Myc oncoproteins. Furthermore, our findings provide support for the use of HDAC inhibitor therapy in cancer types overexpressing Myc oncoproteins and suggest that therapies that augment the expression or function of TG2 may have a synergistic therapeutic effect on cancer when combined with HDAC inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Because TG2 has been demonstrated to suppress tumor growth, metastasis, and angiogenesis in animal models of colon cancer and melanoma (36,37), our findings highlight TG2 as a potential drug development target for the treatment of cancers overexpressing Myc oncoproteins. Furthermore, our findings provide support for the use of HDAC inhibitor therapy in cancer types overexpressing Myc oncoproteins and suggest that therapies that augment the expression or function of TG2 may have a synergistic therapeutic effect on cancer when combined with HDAC inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…40 Although ECs are a rich source of TG2, 41 the presence of TG2 produced by the HFF-1 might be one of the reasons for the observed inhibition of EC assembly into capillary-like structures, as it has already been described that the addition of exogenous TG2 blocks angiogenesis in vitro. 42 In the present work, HUVECs were found to express TG2 when cultured alone for 7, 14, and 21 days (data not shown). However, expression of TG2 was not observed when formation of capillary-like structures occurred, namely in cocultures of HUVEC/HDF (data not shown), which corroborates the fact that the presence of TG2 produced by HFF-1 fibroblasts might be an inhibitor of the formation of capillary-like structures.…”
Section: Ecm Production By the Different Cellsmentioning
confidence: 80%
“…Recombinant TG2 applied to rat mammary adenocarcinomas implanted in dorsal skin window chambers produced significant growth delay in the tumors (34), and transfection of TG2 into a highly malignant hamster fibrosarcoma cell line led to significant reduction of tumor incidence (35). A recent report showed that exogenous TG2 inhibited angiogenesis and tumor growth, and tumor growth in TG2 knockout mice was enhanced (36). These results implicate TG2, like GPR56, as a suppressor of tumor growth.…”
Section: Gpr56 Is a Gpcr Implicated In Multiple Biologicalmentioning
confidence: 86%